INVESTIGATING THE VARIATIONS OF HORIZONTAL (H) AND VERTICAL (Z) COMPONENTS OF THE GEOMAGNETIC FIELD AT SOME EQUATORIAL ELECTROJET STATIONS - Akpaneno, Aniefiok; Abdulahi, O. N. (FUDMA JOURNAL OF SCIENCES, 2021)
This research is monitoring equatorial geomagnetic current which causes atmospheric instabilities and affects high frequency and satellite communication. It presents the variations of Horizontal (H) and vertical (Z) component of the geomagnetic field at some Equatorial Electrojet (EEJ) Stations during quiet days. Data from five (5) observatories along the magnetic equator were used for the study. Daily baseline values for each of the geomagnetic element ð» and Z were obtained. The monthly average of the diurnal variation and the seasonal variations were found. Results showed that the variations of the geomagnetic element of both H and Z differ in magnitudes from one stations to another along the geomagnetic Equator due to the differences of their geomagnetic latitude. The Amplitude curves for Z) are seen to be conspicuously opposite to that of H), and there is absence of CEJ in Z- Component but present in H- Components. The  values during the pre-sunrise hours are low compare to daytime hours. Minimum variations of dH was observed during June solstice and maximum variations was observed during Equinox season. This study shows that daily variations of (H) and (Z) occur in all the stations. The enhancement in H is as a result of EEJ current.